Simbolisme Ritual, Pengalaman K Analisis Simbolisme Ritual dan Pengalaman Keagamaan dalam Kerangka 'Sacred Canopy' di Gereja Masehi Advent Hari Ketujuh Kayu Putih, Jakarta Timur - Kamila Rahma Shalehah, Kamila Rahma Shalehah (IAIN Ambon, 2024)
Starting from its uniqueness, the Adventist Church is known for its strong symbolism in its religious practices. Joachim Wach's phenomenological approach is integrated with Rudolf Otto's Numinous theory and Peter L. Berger's Sacred Canopy theory, which emphasizes the importance of understanding the subjective experiences of congregation members. This research can provide insights into the interaction between ritual symbolism and broader religious experiences in giving meaning to human life within the framework of the